Analisis Dampak Keberadaan Transportasi Online Pada Pendapatan Dan Kesempatan Kerja Tukang Becak (Studi Kasus Kec. Panyabungan Kota Kab. Mandailing Natal) - Nur, Lailan; Rhokan, Mustapa Khamal; Inayah, Nurul (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2023)
The development of information technology in Indonesia has experienced a rapid increase in this modern era. One of these technological developments is the internet which is the result of information technology that covers the whole world, where the internet is used to improve people's welfare from both the economic, health and educational aspects. the only online transportation business. The appearance of online transportation has shaken users or other transportation workers, especially pedicab drivers. Therefore, this study aims to determine the effect of the emergence of this online transportation on pedicab drivers, especially on their income and employment opportunities. This study uses a qualitative method. Data collection techniques in this study by observing and interviewing. Based on the results of observations and interviews conducted, the existence of this online transportation can make the income of pedicab drivers decrease, while in job opportunities many pedicab drivers have switched professions to online transportation, but pedicab drivers who remain in their profession make this a motivation to work. In addition, the community responds that the existence of online transportation has a good influence because it makes their activities easier, but there are also those who do not feel affected because of a lack of knowledge of technology.